Analisa dan Desain Kembali Aplikasi Galeri Lembaga Adat Melayu Riau Menggunakan Metode Design Thinking - Wirasatria Putra; Muhammad Affandes; Yelfi Vitriani; Iwan Iskandar (JURIKOM (Jurnal Riset Komputer), 2022)
Application Galeri Lembaga Adat Melayu Riau or abbreviated as Galeri LAM is a buying and selling application that aims to preserve Budaya Melayu Riau at Sentra Ekonomi Kreatif dan Budaya in collaboration with PT Pertamina and is shaded by the Lembaga Adat Melayu Riau. In this project, there are 3 business processes, namely the Online Store application, supplier and cashier application. What will be discussed in this Journal is the Online Store application. Galeri LAM online store application provides facilities for UMKM Partners to market their products by working with Galeri LAM as a container. Based on the fungski, the Galeri LAM Online Store Application aims to make it easier for UMKM Partners who work together to market their products widely, reach more audiences and as a promotional medium. This application also makes it easier for buyers to find original quality products from RIAU. But in its use there are still many problems. This research focuses on developing application recommendations by analyzing and redesigning the UI and UX of the Galeri LAM Online Store Application using the Design Thinking method. This method is known as a comprehensive thinking process that concentrates on creating solutions that begin with a process of empathy for a certain human-centered need. There are 5 stages in this method, namely Empathize, Define, Ideate, Prototype, and Testing. Application recommendations are built in the form of prototypes using the Figma application. The prototype that was built was successfully tested on 10 respondents using System Usability Scale (SUS) testing and 76 application prototypes